2017
DOI: 10.3389/fpsyg.2017.02069
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School Climate and School Identification on Academic Achievement: Multilevel Modeling with Student and Teacher Data

Abstract: School climate is a leading factor in explaining student learning and achievement. Less work has explored the impact of both staff and student perceptions of school climate raising interesting questions about whether staff school climate experiences can add “value” to students' achievement. In the current research, multiple sources were integrated into a multilevel model, including staff self-reports, student self-reports, objective school records of academic achievement, and socio-economic demographics. Achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(177 citation statements)
references
References 110 publications
7
126
0
16
Order By: Relevance
“…The school environment plays an important role in children's cognitive development and educational outcomes. School climate has been identified as a powerful multidimensional construct associated with children's mental and physical health (Cohen et al., ; Denny et al., ; Gilstad‐Hayden et al., ; LaRusso et al., ; Maxwell, Reynolds, Lee, Subasic, & Bromhead, ; Shochet et al., ; Thapa et al., ; Wang, ; Way et al., ) and academic achievement (Bond et al., ; Brand et al., ; Wang & Holcombe, ). The goals of this study were to examine associations of school climate with children's cortical structure (cortical thickness and surface area) and EF, and to explore the role of school climate as a mediator or moderator of socioeconomic differences in cortical structure and EF.…”
Section: Discussionmentioning
confidence: 99%
“…The school environment plays an important role in children's cognitive development and educational outcomes. School climate has been identified as a powerful multidimensional construct associated with children's mental and physical health (Cohen et al., ; Denny et al., ; Gilstad‐Hayden et al., ; LaRusso et al., ; Maxwell, Reynolds, Lee, Subasic, & Bromhead, ; Shochet et al., ; Thapa et al., ; Wang, ; Way et al., ) and academic achievement (Bond et al., ; Brand et al., ; Wang & Holcombe, ). The goals of this study were to examine associations of school climate with children's cortical structure (cortical thickness and surface area) and EF, and to explore the role of school climate as a mediator or moderator of socioeconomic differences in cortical structure and EF.…”
Section: Discussionmentioning
confidence: 99%
“…Our model confirmed that, in order to promote subjective well-being, schools must facilitate the optimal development of people by accepting that all students possess differentiated strengths, recognize its students' abilities, and offer school environments that imply positivity in aspects concerning the physical, social, and didactic spheres of school life. Insights into these aspects are expected to contribute to a better understanding of how they correspond harmoniously with the abilities and expectations of the students (Corral-Verdugo et al, 2015;Maxwell et al, 2017). The potential implementation of these findings has been widely described in literature.…”
Section: Resultsmentioning
confidence: 96%
“…Such remarks allow for some reassurance that we have established some of the variables that could influence a positive school climate (Bosworth et al, 2011;Aldridge and McChesney, 2018). In the three dimensions proposed by the model, we can also identify the actions required in order to impact on wellbeing and its relationship with the academic achievement of the students (Maxwell et al, 2017), their ways of relating to teachers (Roorda et al, 2011), and the relationships they establish with peers and others in their environment (Tian et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These four variables were selected based on a model proposed by Scheerens (2008) related to 'Basic system model on the functioning of education'. Studies by Al-Raqqad et al, (2017), Bandura, (19931997), Bietenbeck (2011), Ismail et al (2017), Reynolds et al (2017) and Wang and Degol, (2015) stated that all four variables may predict science achievement. The selection of these four factors is also the limitation of the research which is determined by the researcher intentionally but can provide useful information to science education research especially on the effect of non-cognitive factors on achievement at the secondary school level.…”
Section: Timss-based Studiesmentioning
confidence: 99%